Presenting a Model of Factors Influencing Fraud and Financial Misconduct in the Public Sector - Shanazaree, Mojtaba; Kamali, Ehsan; Khani, Naser (Business, Marketing, and Finance Open, 2024)
Fraud and financial misconduct are recognized as fundamental challenges within the financial and accounting systems of the public sector in many countries, particularly in developing countries. In the present study, employing a qualitative grounded theory approach, a model of factors influencing fraud and financial misconduct in the public sector was developed. Accordingly, through conducting interviews with fifteen experts from the Supreme Audit Court and Directors General and Chief Financial Officers of executive agencies, each with 15 years of professional experience and holding master’s and doctoral degrees, seven main categories were identified based on the paradigm model using MAXQDA software and were structured into six dimensions: organizational management style and characteristics of the administrative system as “causal conditions,” external pressures as “intervening conditions,” cultural factors as “contextual conditions,” incentives for misconduct within the human resource management system as the “interactional dimension,” characteristics of accounting and auditing laws and regulations as the “central phenomenon,” and performance consequences as the “outcome dimension.” Furthermore, the highest frequency was related to the variables of administrative system characteristics and the characteristics of accounting and auditing laws and regulations, indicating the greater importance of these variables. Contrary to many previous studies that primarily emphasized managerial factors and legal frameworks, it was found that organizational culture and societal culture, as well as external pressures—including political factors and the country’s institutional environment—also have a significant impact on financial misconduct.